(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The European Court of Human Rights (ECtHR) is the most famous and perhaps the most successful institution of the Council of Europe (CoE). Within the CoE, there is an informal opinion that the Court is a "victim" of its own success. The ECtHR has been continuously facing an increasing influx of applications by European citizens pointing to human rights violations. This phenomenon has necessitated the implementation of effective reforms, both in the European Convention on Human Rights (ECHR) and in the modalities of functioning of the ECtHR. This paper analyzes the effects of reforms that have been implemented over the years, with regard to the basic text of the ECHR, with a focus on the efficiency of the functioning of the Court as well as the overall system related to the protection of human rights. To that end, a special review is made of the content of the declarations arising from high level conferences organized by certain Member States during their chairmanship of the Committee of Ministers. In this context, this paper analyzes the declarations that arise as a result of high-level conferences in Interlaken, Izmir, Brighton, Brussels and Copenhagen.